Pengaruh Motivasi, Pelatihan Dan Komunikasi Terhadap Kinerja Karyawan Pada Perusahaan Daerah Air Minum Tirtanadi Cabang Berastagi - Susi Br Gurusinga; Herlina Novita; Dewi Indriani Sinaga; Melda Fitri Yanti Simamora; Ruth Sania Novaresita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This research was conducted to determine the influence of motivation, training, and communication on the performance of employees at the Tirtanadi Drinking Water Regional Company Berastagi Branch. This type of research uses descriptive research. The number of research samples as many as 52 employees of Tirtanadi Drinking Water District Company Berastagi Branch. The results showed that partially motivation, training, and communication significantly affect the performance of employees at the Tirtanadi Drinking Water Regional Company Berastagi Branch. Simultaneous test results showed that motivation, training, and communication significantly affected the performance of employees at the Tirtanadi Drinking Water Regional Company Berastagi Branch. The influence of motivation, training, and communication on employee performance at Tirtanadi Drinking Water District Company Berastagi Branch by 70.9%. Keywords: Training, Training, Communication, Office Employees